Legal Protection for Consumers on the Transfer of Remaining Shopping Coins into Donations (Case Study at Hypermart Surabaya) - Ricardo Tjandra; Juliana Makadala (Dinasti Research, 2024)
This final project was written based on the author's experience, who often shopped at minimarkets, supermarkets, and hypermarkets. Cashiers usually take unilateral actions in returning the change, tiny denominations, and often harm consumers. Therefore, the author is interested in compiling a final project titled